FREQUENCY STANDARDS : Precise modulation of laser radiation by an acousto-optic modulator for stabilisation of the Nd : YAG laser on optical resonances in molecular iodine. (1st June 2016) - Denisov, V I; Ignatovich, S M; Kvashnin, N L; Skvortsov, M N; Farnosov, S A
Abstract: A system of precise frequency modulation of laser radiation by an acousto-optic modulator, which makes it possible to stabilise the radiation power and simultaneously suppress the residual amplitude modulation to a level of 10 -8 of the total laser power at the third harmonic of modulation frequency (∼500 Hz), is presented. The use of this system for the Nd : YAG/I2 optical frequency standard and application of digital signal synthesis and processing methods provided a level of frequency standard instability as small as ∼10 -15 for ∼6 × 10 4 s.